A unique case of late-onset CIPO caused by a missense mutation in the long isoform of FLNA - D’Amato, Ilaria; Ganguzza, Enrico; Basilisco, Guido; Strippoli, Alessia; Salvi, Erika; Mehmeti, Elkadia; Chiappori, Federica; Devigili, Grazia; Vecchi, Maurizio; Lauria, Giuseppe; Marchi, Margherita (Frontiers in Genetics, 2025)
Mutations in the filamin A (FLNA) gene cause a broad range of disorders, affecting musculoskeletal, nervous, vascular, and gastrointestinal systems, collectively known as filaminopathies. In contrast to previously described mutations in the long isoform of FLNA, which alter the reading frame and lead to loss of Filamin A expression resulting in congenital short bowel syndrome or chronic intestinal pseudo-obstruction in pediatric patients, here we present the clinical and genetic features of an adult patient with chronic intestinal pseudo-obstruction in whom whole exome sequencing revealed a novel missense mutation (p.Gly19Val) in FLNA gene. The onset of symptoms was at 31 years old when he began experiencing constipation, vomiting, and weight loss. Segregation analysis showed that the p.Gly19Val mutation was inherited from the heterozygous unaffected mother and was absent in the healthy brother and father, consistent with X-linked recessive inheritance. The mutation was localized in the N-terminus of the FLNA long isoform, a critical region for smooth muscle contractility and intestinal motility. Structural modeling of the mutant Filamin A suggested that the p.Gly19Val substitution alters the local protein folding and may interfere with the protein ability to cross-link actin filaments, potentially impairing cytoskeletal dynamics in visceral smooth muscle cells. Our study broadens the phenotypic spectrum of filaminopathies and deepens the understanding of the genetic mechanisms underlying chronic intestinal pseudo-obstruction in adults.